Mapping of Research Projects Conducted by the National Council of Educational Research and Training : An Analytical Study - Jain, Pooja; Meera (JOURNAL OF INDIAN EDUCATION, 2024)
National Council of Educational Research and Training (NCERT) is the premier institution in the country dedicated to achieving the highest standards in both school education and teacher training nationwide. NCERT focuses on holistic and multidisciplinary education to develop individuals’ intellectual, professional, aesthetic, social, physical, emotional and moral capacities. This includes Arts, Humanities, Languages, Sciences, Social Sciences, Vocational and Technical fields with bunch of communication, and socio-cultural skills to develop a civilised citizen for the country. This paper provides an in-depth analysis of research projects conducted by NCERT faculty members in various areas of school education during the financial years 2017 2022, as outlined in NCERT’s Annual Reports. The study aims to identify the year-wise distribution of research projects, the educational stages under focus, specific areas of concentration within school education and the geographical scope of these research endeavors. The findings will serve as a guide for NCERT to pinpoint focused areas and address research gaps, offering a foundational reference for similar research initiatives by institutions with a primary research mandate. This study holds particular relevance in the context of India’s large and diverse population, encompassing various languages, cultures, standards of living, and social values.